The influence of inherited continental margin structures on the stress and strain fields of the south-central Taiwan fold-and-thrust belt. Issue 1 (10th July 2019) - Biete, Cristina; Brown, Dennis; Lund, Björn; Alvarez-Marron, Joaquina; Wu, Yih-Min; Kuo-Chen, Hao; Ho, Chun-Wei
SUMMARY: In this paper we test whether or not structural and morphological features inherited from the Eurasian continental margin are affecting the contemporary stress and strain fields in south-central Taiwan. Principal stress directions (σ1, σ2 and σ3 ) are estimated from the inversion of clustered earthquake focal mechanisms and the direction of the maximum compressive horizontal stress ( S H ) is calculated throughout the study area. From these data the most likely fault plane orientations and their kinematics are inferred. The results of the stress inversion are then discussed together with the directions of displacement, compressional strain rate and maximum shear strain rate derived from GPS data. These data show that there is a marked contrast in the direction of S H from north to south across the study area, with the direction of S H remaining roughly subparallel to the relative plate motion vector in the north, whereas in the south it rotates nearly 45° counter-clockwise. The direction of the horizontal maximum compression strain rate (εH ) and associated maximum shear planes, together with the displacement field display an overall similar pattern between them, although undergoing a less marked rotation. We interpret the southward change in the S H, εH and the dextral maximum shear plane directions, together with that of the horizontal displacement field to be related to the reactivation of east–northeast striking faults inherited from the rifted Eurasian margin and to the shelf/slope break. Inherited faults in the basement are typically reactivated as strike-slip faults, whereas newly formed faults in the fold-and-thrust belt are commonly thrusts or oblique thrusts. Eastwards, the stress inversions and strain data show that the western flank of the Central Range is undergoing extension in the upper crust. S H in the Central Range is roughly parallel to the relative plate convergence vector, but in southwestern Taiwan it undergoes a marked counter-clockwise rotation westwards across the Chaochou fault. Farther north, however, there is no significant change across the Lishan fault. This north to south difference is likely due to different margin structures, although local topographic effects may also play a role.